Variability of trace metals in coastal and estuary: Distribution, profile, and drivers. (January 2022) - Harmesa; Wahyudi, A'an Johan; Lestari; Taufiqurrahman, Edwards
Abstract: Ongoing global changes such as increasing sea-surface temperatures, decreasing acidity levels, and expanding oxygen-minimum zone may impact on the biogeochemical cycles of trace metals in ocean systems. Each trace metal has unique characteristics and a distinctive distribution pattern controlled by chemical, biological, and physical processes that occur in ocean systems. The correlations of variability drivers in trace metals are interesting topics for investigation. Following up on ocean research in the coastal and estuary area, we specifically review the distribution of trace metals in seawater and suspended and surface sediment. The marginal seas usually feature significant terrestrial inputs accompanied by several active water-mass currents. The purpose of this review is to provide an overview of variability related to trace-metal distribution in coastal and estuary systems and to specifically describe the distribution, profile and drivers that affect trace metals variability. Highlights: Trace-metal distributions in ocean systems have been classified into conservative-, nutrient-, and scavenged-type profiles Several variability drivers of trace metals may be involved in differences of metal distribution in particular ocean systems The availability of dissolved trace metals is likely to increase in the future due to increasing SST, decreasing pH or decreasing DO Suspended matter which generally derives from terrestrial input plays a role in determining the fate of trace metals The study findings improve our understanding of trace-metal characteristics in the marine environment